Chemicals of concern in select packaged hair relaxers available on the Kenyan market: an examination of ingredient labels and measurement of pH - Irungu, Beatrice N.; Llanos, Adana A. M.; Nyangi, Mary; Olisa, Teresa; Matu, Esther; Rockson, Amber; Schaefer, Alexis; Ashrafi, Adiba; Terry, Mary Beth; McDonald, Jasmine A.; Nudelman, Janet; Gillan, Laura Dobbs; et al. (Frontiers in Public Health, 2025)
BackgroundThere is an emerging interest in the investigation of hair relaxers as important sources of exposure to chemicals of concern (CoCs) and their associated adverse health effects. We focused on documentation of CoCs by examining labels of selected relaxers currently available on the market in Nakuru and Embu Counties, Kenya and measured the pH profiles to ensure compliance with Kenya Bureau of Standards.MethodsWe enrolled 746 women aged 15–50 years in a cross-sectional study, which ascertained participants’ sociodemographic characteristics, personal care products use in the last 7–14 days and ever use of hair dyes and chemical relaxers including the brand names of products used. Based on participants’ questionnaire responses and product availability at beauty shops and supermarkets, we purchased 22 different relaxer products. The label of each product was reviewed and we recorded relaxer strength, manufacturer and location, listed ingredients, and other claims. To identify CoCs, we cross-checked the list of ingredients against the Campaign for Safe Cosmetics’ (CSC) Red List and European Union’s prohibited and restricted substances (Annex II and III respectively), Regulation 1223/2009 on cosmetics. The pH profiles of each product were determined using a benchtop pH meter.ResultsTwenty-seven CoCs were documented upon examination with each relaxer listing more than one CoC. Thirteen out of 27 (48.2%) were fragrance chemicals with d-limonene/limonene and linalool, each being listed as an ingredient in 9 products. Fourteen (63.6%) relaxers had undisclosed ingredients listed as ‘fragrance’ and/or ‘parfum’. Six of the identified CoCs are classified as Tier 1 (Do not use for everyone) per CSC Red List while 14.8% (4) are prohibited and 55.6% (15) are restricted substances per EU regulations. The pH values of the relaxers were within Kenya Bureau of Standards required range of 11–13.ConclusionThese findings create awareness of CoCs listed on labels of selected hair relaxers. This justifies the need for consumer education on potentially harmful chemicals and their associated risks. Further, our findings justify the need for laboratory study to evaluate and quantify CoCs that are listed as well as those that are not listed on the label.